2016
DOI: 10.1634/theoncologist.2016-0126
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Management and Outcomes in Waldenström Macroglobulinemia: A Population-Based Analysis

Abstract: Most older patients with Waldenström macroglobulinemia currently treated in the U.S. receive rituximab as monotherapy or in combination with bortezomib or bendamustine. Newly designed trials should consider control arms aligned with this prevalent real-life standard. Compared with the 1990s, patients diagnosed according to current criteria are more likely to have anemia or neuropathy, or to receive early chemotherapy, but only 2.5% require plasmapheresis at diagnosis. The incremental clinical value of newly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…Approximately, one-third of patients needed therapy at the time of diagnosis and half of the patients needed therapy within 1 year from diagnosis. This finding is similar to the observations from a population-based study in WM patients aged 65 or older (Olszewski et al, 2016). Our study suggests encouraging OS rates in young WM patients.…”
supporting
confidence: 92%
“…Approximately, one-third of patients needed therapy at the time of diagnosis and half of the patients needed therapy within 1 year from diagnosis. This finding is similar to the observations from a population-based study in WM patients aged 65 or older (Olszewski et al, 2016). Our study suggests encouraging OS rates in young WM patients.…”
supporting
confidence: 92%
“…Olszewski et al in 2016 estimated that novel treatments, adopted as a standard of care, may lead to observable changes in both survival and costs of therapy [40]. In the study, mean total Medicare payments for the care of a patient with WM at 15 years from diagnosis were calculated to be $163,432 (€147,301).…”
Section: Discussionmentioning
confidence: 93%
“…Only a few economic studies were identified while neither cost-effectiveness analyses nor economic evaluations on ibrutinib for WM, published in full, were found [2,40].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that it is a common practice in the US to offer single agent rituximab as primary therapy in WM patients (Olszewski et al , ). However, we consider single agent rituximab a less effective therapy in WM, which is associated with an ORR of 30–40% and median PFS ranging between 1 and 2 years (Gertz et al , ; Treon et al , ).…”
Section: Discussionmentioning
confidence: 99%